2007
DOI: 10.1038/sj.emboj.7601628
|View full text |Cite
|
Sign up to set email alerts
|

An alternative branch of the nonsense-mediated decay pathway

Abstract: The T-cell receptor (TCR) locus undergoes programmed rearrangements that frequently generate premature termination codons (PTCs). The PTC-bearing transcripts derived from such nonproductively rearranged genes are dramatically downregulated by the nonsense-mediated decay (NMD) pathway. Here, we show that depletion of the NMD factor UPF3b does not impair TCRb NMD, thereby distinguishing it from classical NMD. Depletion of the related factor UPF3a, by itself or in combination with UPF3b, also has no effect on TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
270
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(297 citation statements)
references
References 62 publications
24
270
3
Order By: Relevance
“…Tight control of NMD factor concentrations through autoregulation buffers such undesired consequences. Previously, individual NMD factor-encoding mRNAs have already been reported to be targeted by NMD in different organisms: SMG5 has been identified as an NMD target in human and fruit fly cells (Mendell et al 2004;Rehwinkel et al 2005;Chan et al 2007), SMG7 and UPF3 in plants (Kerenyi et al 2008;Saul et al 2009), SMG6 in fruit fly (Rehwinkel et al 2005), and UPF1 in mouse (Weischenfeldt et al 2008). Thus the selfregulation of NMD that we demonstrated in this study for human cells likely extends to other organisms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Tight control of NMD factor concentrations through autoregulation buffers such undesired consequences. Previously, individual NMD factor-encoding mRNAs have already been reported to be targeted by NMD in different organisms: SMG5 has been identified as an NMD target in human and fruit fly cells (Mendell et al 2004;Rehwinkel et al 2005;Chan et al 2007), SMG7 and UPF3 in plants (Kerenyi et al 2008;Saul et al 2009), SMG6 in fruit fly (Rehwinkel et al 2005), and UPF1 in mouse (Weischenfeldt et al 2008). Thus the selfregulation of NMD that we demonstrated in this study for human cells likely extends to other organisms.…”
Section: Discussionmentioning
confidence: 77%
“…Whereas the link between AS and NMD is well established in that one-third of alternatively spliced transcripts contain PTCs (Lewis et al 2003) and that many core spliceosomal components are under NMD regulation (Saltzman et al 2008), the autoregulation of the NMD pathway has been less appreciated so far. It was shown that SMG5 and SMG6 were targets of feedback regulation in Drosophila cells (Rehwinkel et al 2005), SMG7 and UPF3 were targeted by NMD in plants (Kerenyi et al 2008;Saul et al 2009), and SMG5 was induced under UPF1 depletion conditions in HeLa cells (Mendell et al 2004;Chan et al 2007), but in a different study of NMD inhibition by UPF2 KD in HeLa cells, the levels of UPF1, UPF3a, UPF3b, SMG5, and SMG6 remained unchanged (Wittmann et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Before investigating the role of UPF1 in gene regulation, we validated to be essential for all types of NMD. [34][35][36][37][38] Thus, UPF1 is functionally the most important NMD factor and is the most evolutionarily conserved. 39,40 UPF1 also acts in non-NMD decay pathways, such as staufen1 (STAU1)-mediated mRNA decay (SMD) and replication-dependent histone mRNA decay.…”
Section: Resultsmentioning
confidence: 99%
“…As a corollary of this scenario, not all NMD targets would be cleaved by SMG6; and those that are not may depend partly on the SMG5-SMG7 complex for degradation. Finally, an alternative, UPF3-independent branch of the NMD pathway has been described (Chan et al 2007), suggesting that UPF3 may not always compete with SMG6 for EJC binding.…”
Section: When Does the Smg6-ejc Interaction Occur?mentioning
confidence: 99%